Health-Related Quality of Life Among Type 2 Diabetes Patients With Depressive Symptoms in Vietnam - Nguyen Tran Kien; Nguyen Phuong Hoa; Ha Huu Tung; Kris Van den Broeck; Johan Wens (Journal of Diabetes Research)
Conclusion: The findings underscore the critical need for integrated care approaches that include mental health support for T2DM patients. Routine screening for depressive symptoms should be a component of diabetes management protocols to improve overall patient outcomes. Further longitudinal research is needed to confirm these findings and develop effective interventions.